Nutritional study of an Olympic Spanish athlete (20km walk men) during two weeks in CAR of Sierra Nevada (Spain) - Mariscal-Arcas, M.; Molina, J. M.; Monteagudo, C.; Martin, T.; Fernández de Alba, M. C.; Olea-Serrano, F. (Archivos de medicina del deporte, 2008)
Many elite runners have low total body weights, being small in stature and lightly muscle. Most runners will find that the typical western diet does not provide sufficient energy race training. Energy needs also increase because of the elevated energy expenditure with physical activity Carbohydrate intake after the session or race will ensure you meet carbohydrate needs before the next training session. Distance runners, particularly females, are at a high risk of low iron status. Many runners look like they eat adequate dietary iron but on closer examination, this can be mostly plant based iron food that are not well absorbed. It is important to know your sweat losses and drink fluid accordingly Fluid intake to ensure the replacement of water and electrolytes lost in sweat is important. Objective: To evaluate the intake of antioxidant nutrients, as important components of the diet of sport people. Material and method: A Dietary Antioxidant Quality Score (DAQS) was computed considering the risk of inadequate intakes for selenium, zinc, Beta-carotene, vitamins C and E. This score (ranged 0, very poor DAQS, to 5, high quality diet) Competitive athletes are thought to have a much greater likelihood of antioxidant vitamin sub-deficiency status as a result of an increased O2 utilization. Athletes therefore represent a population potentially exposed to oxidative damage. In addition, alterations of the antioxidant status in athletes could also be related to specific deficiencies resulting from inadequate and unbalanced dietary intakes. Results: This study analyze ten days diet of a runner (20Km walk) and estimated mean of energy 4147.0Kcal (SD:442.8): 20.5% from proteins, 56.3% from carbohydrates and 26.1% from lipids. Mean of DAQS is high quality diet 4.80 (SD: 0.42). Conclusion: These runner have a balanced diet.